Socioecological revitalization of an urban watershed. Issue 1 (11th January 2013) - Hager, Guy W; Belt, Kenneth T; Stack, William; Burgess, Kimberly; Grove, J Morgan; Caplan, Bess; Hardcastle, Mary; Shelley, Desiree; Pickett, Steward TA; Groffman, Peter M
Abstract : Older, economically troubled urban neighborhoods present multiple challenges to environmental quality. Here, we present results from an initiative in Baltimore, Maryland, where water‐quality improvements were rooted in a socioecological framework that highlighted the interactions between biogeophysical dynamics and social actors and institutions. This framework led to implementation of best management practices followed by assessment of changes in human perception, behavior, and education programs. Results suggest that such an initiative can improve both water quality (eg reductions in nitrogen and phosphorus runoff) and quality of life (eg increased involvement in outdoor recreation by residents and improvements in student environmental literacy and performance) in urban neighborhoods. However, proposed solutions to the water‐quality problems in such neighborhoods have (1) typically emphasized the need for stormwater facilities that are difficult to build and maintain and (2) comprehensively addressed neither the issues related to aging infrastructure and hydrologic complexity nor the benefits derived from linkages between resident perception of environmental improvements and behavior and water‐quality outcomes.